An innovative outcome-based care and procurement model of hemophilia management. (3rd May 2016) - Gringeri, Alessandro; Doralt, Jennifer; Valentino, Leonard A.; Crea, Roberto; Reininger, Armin J.
ABSTRACT: Hemophilia is a rare bleeding disorder associated with spontaneous and post-traumatic bleeding. Each hemophilia patient requires a personalized approach to episodic or prophylactic treatment, but self-management can be challenging for patients, and avoidable bleeding may occur. Patient-tailored care may provide more effective prevention of bleeding, which in turn, may decrease the likelihood of arthropathy and associated chronic pain, missed time from school or work, and progressive loss of mobility. A strategy is presented here aiming to reduce or eliminate bleeding altogether through a holistic approach based on individual patient characteristics. In an environment of budget constraints, this approach would link procurement to patient outcome, adding incentives for all stakeholders to strive for optimal care and, ultimately, a bleed-free world.